ANCIENT ROMAN TRADITIONS IN THE DECORATION OF ENVIRONMENT - Danylenko, Olha (Вісник КНУКіМ. Серія «Мистецтвознавство», 2015)
The article describes the evolution of the existence of the Roman traditions in the decoration of environment. Inherited from the Greeks, the ideas of humanism are claimed to have contributed to awakening the personality, as well as to the creative development of the architectural thought. Due to this, the urban town-planning canons and traditions of the Roman decorative art were entrenched at such a high level that they are adhered to at the present stage either, while being creatively developed and improved.